Relative age effects in track-and-field: Identification and performance rebalancing - Difernand, A.; De Larochelambert, Q.; Homo, S.; Rousseau, f.; Antero, J.; Toussaint, J.-F.; Sedeaud, A. (Frontiers in Physiology, 2023)
Introduction: Relative Age Effect (RAE) consists of a biased distribution of the dates of birth in a same-age group.